Improving Growth and Carcass Production of Rabbit by Utilization of Curcuma xanthorrhiza Roxb on Ration - Haryanto, Budi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The research aimed to study the improvement of growth and carcass production of rabbits through the use of temulawak (Curcuma xanthorrhiza Roxb) on ration. Â The materials used were 25 heads of male rabbits of New Zealand White breed.Â A Randomized Completely Block Design was used with five treatments, which were kinds of diet based on Curcuma xanthorrhiza Roxb levels. Â Body weights were treated as blocks.Â Variables measured consisted of dry matter consumption, growth (body weight gain) and carcass production (carcass weight). Â Data was analysis using Multivariate Analysis.Â Results revealed that the highest feedâs dry matter consumption was in C3 (135.42 g/head/day), the lowest was in C0 (93.23 g/head/day).Â Â The C3, C2, and C4 treatments were significantly difference (P<0.05) to C0. The C2, C3 and C1 were significantly difference (P<0.05) to C0.Â The highest body weight gain (18.85 g/head/day) was in C2, and the lowest were in C0 (12.71 g/head/day), and the highest carcass weight (989 g) based on slaughter weight was in C3, and the lowest (711 g) was in C0. (Animal Production 8(3): 190-195 (2006)Â Key Words : Rabbit, growth, carcass weight, Curcuma xanthorrhiza Roxb